Penggunaan Model Discovery Learning Untuk Meningkatkan Proses Pembelajaran Tematik Terpadu di Sekolah Dasar - Hartina, Titri; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research purposed to describe Use Of Discovery Learning Model To Improve  Integrated Thematic Learning In Elementary School. This research is a classroom action research with qualitative and quantitative approaches. Subjects were teachers and 23 students. This research was consists of two cycles. The first cycle consists of two meetings and the second cycle consists of one meeting with stages of planning, implementation, observation, and reflection . The result of planning observation in cycle I  is 81,81% (B) and it increase to be 93,18% (SB)  in cycle II. The result of teacher aspect observation in cycle I is 81,25% (B)  and it increase to be 93,75% (SB) in cycle II. The result of student aspect observation in cycle I is 81,25% (B)  and it increase to be 92,15% (SB) in cycle II. The learning outcomes in cycle I is 82,12 (B) and it increase to be 92,15% (B) in cycle II. The research showed the model discovery learning can improve the integrated thematic learnig process in Elementary School